Sistem Informasi Peramalan Obat Alphamol Menggunakan Metode Double Exponential Smoothing - Evy Sophia; Jauharul Maknunah; Mohamad Dimas Oktavianda (LPPM UBHINUS MALANG, 2021)
Sofia Medika Clinic in terms of supply of alphamol drugs every month is always the same, because the clinic has not been able to predict the number of drugs that need to be provided. When the amount of drug inventory is in excess, it will result in fewer drug expiration dates and make the selling price of drugs cheaper. On the other hand, when the amount of drug supply is in short supply, it will have an impact on patient service or buyers who are considered disappointing and have an impact on the clinic. To assist clinics in reducing drug sales errors, a technology is needed in it using forecasting methods. Based on the existing sales data pattern, the forecasting method used is the Double Exponential Smoothing method, because the sales data is a trend with all p-values > 0,05 with the Dicky Fuller test (ADF-test). This study aims to build an Alphamol Drug Forecasting Information System at Sofia Medika Clinic with the Double Exponential Smoothing Method. The results of the alphamol drug sales forecasting application system using the Double Exponential Smoothing Method obtained MAD = 221,0925, MSE = 176693,3, and MAPE = 7,26%. which previously produced a value of 29% so that the results of this application can be used to predict the amount of alphamol drug sales that will be sold in the present and in the future.